Application of Animation Video Media to Learning Outcomes Soccer Passing - AGIDIA DWI VERONIKA SAPUTRI; MOCHAMAD RIDWAN (Universitas Pendidikan Indonesia, 2021)
Introduction: Massive policies from the government resulted in changes in the procedures for learning physical education in schools. In online distance learning, many students and teachers experience unpreparedness in learning. On the one hand it creates new problems because students have to understand the material in different ways and prepare internet quotas, but on the other hand it becomes a means of spreading the word. While Physical Education in schools is the function and purpose of each academic unit that forms individual students who are superior and qualified in all fields. Purpose: This study aims to determine the effect and how much the application of animated video media on the learning outcomes of soccer passing. Methods: This study was a quasi-experimental design with a nonrandomized control group pretest-posttest design. The research population was class VII F and VII H of SMPN 20 Surabaya students in 2021/2022, totaling 33 people. Learning outcomes data were collected through pretest and posttest. Data analysis used normality test, homogeneity test, and t-test with the help of SPSS version 26. Results: In the experimental group, the average value was 94.93. Conclusions: Thus, it can be concluded that animated video media significantly affects soccer passing learning outcomes. It is recommended for teachers to use animated video media because it has become one of the efforts to improve student learning outcomes.